What is the risk of progressive multifocal leukoencephalopathy in patients with ulcerative colitis or Crohn’s Disease treated with vedolizumab? - Card, Timothy R.; Xu, Jing; Liang, Huifang; Bhayat, Fatima (Lippincott, Williams & Wilkins, 2018)
Background: Progressive multifocal leukoencephalopathy is a serious condition linked to certain diseases and immunosuppressant therapies, including the α4 integrin antagonist natalizumab. No cases have been reported to date with vedolizumab, a selective antagonist of the α4β7 integrin expressed on gut-homing lymphocytes. This analysis aimed to describe the current and future expected occurrence of progressive multifocal leukoencephalopathy with vedolizumab use, were the risk the same as in other populations in which this disease has been studied.